2017
DOI: 10.1002/cpt.773
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction and Clinical Use of Cardiac‐Specific Troponin Assays

Abstract: The earliest biomarkers introduced to diagnose myocardial infarction (MI) such as aspartate aminotransferase (AST) and lactic dehydrogenase (LDH) lacked cardiac specificity and were replaced by creatine kinase (CK), the CK‐MB isoenzyme, and ultimately the cardiac‐specific troponins (cTnT and cTnI). This has opened up the possibilities of ruling out MI more rapidly and also identifying patients with a chronic elevation of cTn and a poor prognosis in a range of cardiac conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…They may also undergo considerable improvement in terms of sensitivity or specificity, or both. An excellent example of this is the refinement of the use of blood measurements of cardiac-specific troponin as an indicator of myocardial damage (31).…”
Section: Biomarkersmentioning
confidence: 99%
“…They may also undergo considerable improvement in terms of sensitivity or specificity, or both. An excellent example of this is the refinement of the use of blood measurements of cardiac-specific troponin as an indicator of myocardial damage (31).…”
Section: Biomarkersmentioning
confidence: 99%
“…LDH, CK, CK-MB, and AST were detected to diagnosed myocardial injury. Although these four indicators are not as specific and sensitive as high-sensitivity troponin, they are still classic serum biomarkers of myocardial injury since the 1960s ( 24 ) and are widely used in quite a few clinical trials or animal experiments ( 25 – 27 ). Our findings suggested that NLR was closely associated with the expression of LDH, CK, CK-MB, and the level of 2.967 was the optimal cutoff value for predicting myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Akut Koroner Sendrom (AKS) hastalarının takibinde troponin I, CK, mass CK-MB takibi yapılmaktadır (16) . Tekrarlayan göğüs ağrılarında bu parametreler, reinfarktüs oluşumunun en önemli göstergesidir (17) .…”
Section: Gereç Ve Yöntemunclassified